2016
DOI: 10.1017/s1751731116000823
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the leucine and histidine requirements for piglets fed a low-protein diet

Abstract: Reduction of the CP content in the diets of piglets requires supplementation with crystalline essential amino acids (AA). Data on the leucine (Leu) and histidine (His) requirements of young pigs fed low-CP diets are limited and have primarily been obtained from nonlinear models. However, these models do not consider the possible decline in appetite and growth that can occur when pigs are fed excessive amounts of AA such as Leu. Therefore, two dose-response studies were conducted to estimate the standardised il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
(21 reference statements)
3
13
2
Order By: Relevance
“…In our study we found both similarities and differences for growth performance compared to the previous studies. ADG increased from 70% to 115% SID Leu:Lys which is in contrast with the previous observations 17,18 . This can be explained by the different BCAA levels, especially Val which was at 70 and 72% in the study by Wessels et al .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In our study we found both similarities and differences for growth performance compared to the previous studies. ADG increased from 70% to 115% SID Leu:Lys which is in contrast with the previous observations 17,18 . This can be explained by the different BCAA levels, especially Val which was at 70 and 72% in the study by Wessels et al .…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, a study on pigs of 10–28 kg BW reported a lower ADG in pigs fed 83% SID Leu:Lys compared to 94%, 104% and 115% SID Leu:Lys levels, where ADG was constant. No difference in ADFI and G:F between Leu levels was observed 18 .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…A similar result was also reported by Haug et al (17) that the feed intake of broilers at d 28 was lower with high histidine supplementation in diet. Some researches have reported that histidine have a suppressive effect on food intake (18,19). Both intraperitoneal injection of L-HIS and dietary supplementation of L-HIS suppressed food intake by means of its conversion into histamine in animal’s hypothalamus (20, 21).…”
Section: Discussionmentioning
confidence: 99%